PEMBERANTASAN BUTA HURUF AL-QUR’AN MELALUI METODE AL-JABARI DAN TAHSINUL QUR’AN - Maspuroh, Maspuroh; Tantrayana, Silvia; Suhendi, Ujang; Nursiva, Asri (Dirasa Islamiyya: Journal of Islamic Studies, 2022)
Being able to read the Al-Qur’an is an obligation for every Muslims. The Al-Qur’an is a way of life, the main source of Islamic law, and the main source of Islamic teachings. In the result of field observations conducted in Kademangan Village especially in Pesantren Nurul Hikmah, it was found that many childerns and residents were unable to read the Al-Qur’an well. Therefore, the researcher provides a solution namely by providing an introduction to the method of reading Al-Qur’an Al-Jabari and Tahsinul Quran in the hope that the problems that occur can be solved.